Analisis Kebocaran Gas SF6 Terhadap Kecepatan Busur Api dan Tegangan Tembus pada PMT di GISTET Saguling - Naftalin Winanti; Een Taryana; Gina Nur Sa’adah (EPSILON: Journal of Electrical Engineering and Information Technology, 2022)
Gas Insulated Switchgear Extra High Voltage (GISTET) is a power system component that has a function as a distribution center (transmission) that connects the extra high voltage transmission system through distribution channels or substations. Based on the installation of GISTET equipment, relying on hexafluoride gas (SF_6) as an insulating medium on the equpment. Equipment at GISTET is not always in good condition, GISTET also often experiences problems. One of the distrubances that GISTET often experiences is the leakage of SF6 gas at the PMT (circuit breaker). This requires a treatment called a GISTET overhaul. So in this paper the author will analyze the SSF_6 gas leak as insulation on the PMT (circuir breaker) at GISTET Saguling. According to the results of the calculations in this final project, the gas pressure of SF_6 and the breakdown voltage of PMT are interrelated. At the pressure when the gas leak occurs is at a value below 5kgf/cm2it is able to with stand the voltage. Penetrating with a high value so it is very effective to reduce arc fire. In addition, the SF_6 gas pressure is also related to the arc speed because the lower the pressure value at the time of gas leakage, the arc speed decreases, so the arc will be slow to muffle.